2015
DOI: 10.1210/jc.2014-3855
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of a Novel Angiogenic Factor, Leucine-Rich-α2-Glycoprotein (LRG1), Is Associated With Arterial Stiffness, Endothelial Dysfunction, and Peripheral Arterial Disease in Patients With Type 2 Diabetes

Abstract: Higher LRG1 is a significant predictor for arterial stiffness, endothelial function, and PAD. The pathobiological basis and the temporal relationships of these associations need to be explored by further mechanistic and prospective studies to understand the clinical significance of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 31 publications
8
66
0
Order By: Relevance
“…More recently, we reported, in a cohort of patients with type 2 diabetes, higher circulating LRG1 in those with peripheral arterial disease compared to those without . We observed LRG1 to be positively associated with measures of obesity [body mass index (BMI) and waist circumference].…”
Section: Introductionmentioning
confidence: 75%
See 2 more Smart Citations
“…More recently, we reported, in a cohort of patients with type 2 diabetes, higher circulating LRG1 in those with peripheral arterial disease compared to those without . We observed LRG1 to be positively associated with measures of obesity [body mass index (BMI) and waist circumference].…”
Section: Introductionmentioning
confidence: 75%
“…Plasma LRG1 was measured by commercially available ELISA kits (Immuno‐Biological Laboratories, Gunma, Japan) as described previously . Our intraplate coefficient of variation (CV) was 5.65%, and interplate CV was 9.37%.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic kidney disease (CKD) was defined by the presence of eGFR <60 ml/min/1.73m 2 or kidney damage as indicated by ACR≥30mg/g [23]. Assessment for neuropathy was performed by a neurothesiometer (Horwell Scientific, Wilford, Nottingham, UK) for vibration and with a 10-g monofilament for light touch as described previously [24]. Neuropathy was present if an abnormal finding in monofilament (inability to detect at least 8 of 10 points on either foot) or neurothesiometer testing of ≥ 25 V was detected [24].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, the function of LRG1 in tumors was investigated, and indicated that LRG1 was associated with multiple types of tumor, including ovarian cancer, glioblastoma and squamous cell lung cancer (1518). Furthermore, certain previous studies reported that LRG1 is involved in various diseases, including inflammatory diseases, heart failure, arterial stiffness, endothelial dysfunction and peripheral arterial disease (1923). Previously, LRG1 expression in the brain during aging and neurodegenerative diseases, including idiopathic normal pressure hydrocephalus, Parkinson's disease with dementia, dementia with Lewy bodies, progressive nuclear palsy and Alzheimer's disease was investigated (24,25).…”
Section: Introductionmentioning
confidence: 99%